Kajian Awal Pengembangan E-LKPD Berbasis Deep Learning Untuk Mata Pelajaran Ipa Kelas VIII SMPN 4 Siak Hulu - Rahmahwati, Laily; Hidayati, Nurkhairo (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the need for developing a deep learning–based Electronic Student Worksheet (E-LKPD) for science learning in Grade VIII at UPT SMP Negeri 4 Siak Hulu. The study employed a descriptive quantitative approach to obtain a comprehensive overview of teachers’ and students’ needs related to digital learning media. The research subjects consisted of one science teacher and 36 students of class VIII.2. Data were collected through classroom observations, structured interviews with the science teacher, and questionnaires distributed to students. Interview data were analyzed using descriptive qualitative techniques, while questionnaire data were analyzed quantitatively by calculating the percentage of needs based on predetermined criteria. The results indicated that the need for digital learning media reached 85%, categorized as very high. The suitability of learning media to students’ characteristics obtained a percentage of 80%, also categorized as very high. Meanwhile, the availability and utilization of learning media in schools reached 73%, categorized as needed. Students’ expectations toward the development of a deep learning based E-LKPD reached 80%, indicating a very high level of need. Teacher interview results supported these findings, revealing that digital learning media, particularly E-LKPD, are required to enhance students’ motivation, active engagement, learning independence, and understanding of abstract science concepts. These findings indicate that the development of a deep learning–based E-LKPD is highly necessary as an innovative learning solution to support effective, interactive, and meaningful science learning in accordance with the characteristics of 21st-century learners.